2007
DOI: 10.1038/sj.ejcn.1602594
|View full text |Cite
|
Sign up to set email alerts
|

Determination of free L-carnitine levels in type II diabetic women with and without complications

Abstract: Background: Studies on the determination of carnitine levels and nutritional status in patients of type II diabetes. Objective: We designed this study to determine changes of serum-free L-carnitine in type II diabetic women. Design: A cross-sectional study (case-control study). Setting: Clinical of Endocrinology and Metabolism, Sina Hospital, Pharmacological Research Center, Tabriz Medical university, Iran. Patients and methods: Taking into account the importance of the control of diabetes, in the present case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 23 publications
2
25
0
2
Order By: Relevance
“…This assumption is supported by the lack of fasting ketosis in our GDM population and it is in line with previous studies that reported comparable fasting ketonemia in normal pregnancies and well-controlled GDM [22]. Similarly, studies in diabetic patients showed that the FC levels are not decreased in the absence of diabetes-associated complications [23] or ketosis [24]. In contrast to our results, the only previous study dealing with carnitine levels in diabetic pregnancies reported increased FC and decreased AC in pregnancies complicated with GDM compared to normal pregnancies [9].…”
Section: Discussionsupporting
confidence: 77%
“…This assumption is supported by the lack of fasting ketosis in our GDM population and it is in line with previous studies that reported comparable fasting ketonemia in normal pregnancies and well-controlled GDM [22]. Similarly, studies in diabetic patients showed that the FC levels are not decreased in the absence of diabetes-associated complications [23] or ketosis [24]. In contrast to our results, the only previous study dealing with carnitine levels in diabetic pregnancies reported increased FC and decreased AC in pregnancies complicated with GDM compared to normal pregnancies [9].…”
Section: Discussionsupporting
confidence: 77%
“…Accumulation of long-chain fatty acids and other fatty acid metabolites impair insulin signaling and contribute to the development of insulin resistance in skeletal muscle and heart (18). Some studies reported that subjects with diabetes have reduced plasma free carnitine concentrations compared with healthy subjects, indicating an association between impaired carnitine status and glucose intolerance (18,28,29). All participants in our study had diabetes and experienced significant decreases in HbA 1c after 12 weeks of carnitine-orotate complex treatment compared with no significant change in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…Because CPT1 and CrAT share similar carnitine binding motifs ( 31 ), these data support the notion that carnitine acyltransferases are susceptible to inhibition when local carnitine concentrations fall. This observation is particularly relevant to obesity, diabetes, and other disease conditions associated with carnitine insuffi ciency ( 2,(32)(33)(34)(35)(36)(37)(38)(39)(40). Moreover, results from the current study suggest that the mitochondrial pool of free carnitine is more prone to depletion than other compartments.…”
Section: Discussionmentioning
confidence: 99%